Molecular-based evidence for school transmission of enteroaggregative Escherichia coli among apparently healthy children attending nursery, infant, and primary schools in Madrid (Spain) - Llorente, María Teresa; Salimo Muadica, Aly; Dashti, Alejandro; Köster, Pamela Carolina; Bailo, Begoña; López, Andrea; Carmena, David; Sánchez, Sergio (Springer, 2025)
Information on the epidemiology, transmission dynamics, and public health impact of enteroaggregative Escherichia coli (EAEC) infection in schoolchildren from high-income countries is scarce. This study investigated the occurrence of EAEC infections in apparently healthy children (0-12 years) attending nursery, infant, and primary schools in Spain. High-resolution whole-genome sequencing typing was used to detect and trace back unnoticed episodes of transmission within school settings. An overall EAEC prevalence of 5.1% was observed, with children in the 0-3 age group showing the highest prevalence (24.2%). Besides their gastrointestinal potential, 17% of EAEC isolates revealed an additional urinary/systemic pathogenic potential. Presumptive outbreaks of EAEC infection were identified in two different nursery schools involving the endemic subtypes O126:H27-ST200 (15 children) and O111:H21-ST40 (12 children). Most affected children shared caregivers and common areas including activity, eating, sleeping, and diapering/toileting rooms. Direct person-to-person transmission was highly suspected, although foodborne transmission could not be completely ruled out. Six independent micro-foci of EAEC infections were additionally identified in five different infant and primary schools also involving O126:H27-ST200 (two children) and O111:H21-ST40 (three children), as well as O3:H2-ST10 (three children), O44:H18-ST1380 (two children and two siblings), and ONT:H33-ST34 (four children). No clear information was available on the sources of infection and transmission routes in these settings. Conclusion: Apparently healthy Spanish schoolchildren may be carriers and potential spreaders of certain EAEC subtypes with gastrointestinal/extra-intestinal pathogenic potential. While transmission within school settings appears to be the most likely explanation for the EAEC genomic clusters identified, particularly among toddlers, extra-school infections through alternative pathways cannot be entirely ruled out.